Including stakeholder input in formulating and solving real-world optimisation problems: Generic framework and case study. (May 2016) - Wu, Wenyan; Maier, Holger R.; Dandy, Graeme C.; Leonard, Rosemary; Bellette, Kathryn; Cuddy, Sue; Maheepala, Shiroma
Abstract: Multi-objective evolutionary algorithms (MOEAs) are becoming increasingly popular for solving formal environmental and water resources optimisation problems. In the past, the focus of these studies has generally been on methodological issues related to the optimisation algorithm. However, in recent years, there has been increased recognition of the need to apply these approaches to real-world problems to facilitate the realisation of their full potential. In order to assist with this, a framework for including stakeholder input in real-world optimisation problems is introduced in this paper, including a conceptual framework and a procedure for implementing it. The framework is applied to an urban water supply security study for Adelaide, South Australia. This study highlights the role of stakeholder input at the various stages of the optimisation process, as well as the resulting changes in the formulation, analysis and results. A discussion of the lessons learnt from the case study is also provided. Highlights: Framework for including stakeholder input in evolutionary algorithm optimisation. Stakeholder input included at all stages of optimisation process. Framework applied to urban water supply security study in Adelaide, South Australia.